Unbreakable : the spies who cracked the Nazis' secret code - Barone, Rebecca E. F. (Henry Holt and Company, 2022)
Recounts the true story of how a team of Allied codebreakers, spies, and Navy soldiers broke the Nazi code and helped tip the scales in favor of the Allies during World War II. Profiles the different individuals involved and their contributions. Includes an epilogue, photographs, and a timeline.